(3GdQhV GdRGgQ aj fSH SjOi eMeO WGgQs
(3ChdgG (B:s
(3eMeO SjO gPG GdYUQ GHf eMeO GdLdjd GdbOQ s
(3BNQgG (B:s
(3hgh YeQ Hf YjSi Hf YHO GdhgGH GdMSfi GdYdei , NGQ Gddg dg ai GdOGQjf Bejf s
(3hgh CQLhRI YOO CHjGJgG (B13 (3HjJkGs
(3Ke fbhd Yf GdYdeGAs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdJGQjNs